Financial and sustainable management of the gastronomic industry in special customs regime areas - Rodríguez-Márquez, Ritssy Liney; Angulo-Rangel, Franklin Alejandro; Ustate Pérez, Marili (Revista de Ciencias Sociales, 2025)
The municipalities of Maicao, Uribia, and Manaure, in Colombia, historically face a socioeconomic complexity marked by inequality, natural wealth, and the cultural heritage of the Wayúu indigenous people. The rich local gastronomic industry of ethnic character is driven by the inhabitants themselves from their cultural activities, causing imbalances and precarious states for its efficient exploitation. Therefore, the objective of this documentary-hermeneutic research seeks to analyze the ethnic gastronomic industry of Maicao, Uribia, and Manaure, linking the financial and economic dynamics resulting from the creation of these municipalities of Colombia’s La Guajira as special customs regime zones. Although the creation of this regime dates back more than two decades, local ethnic gastronomy has had little impact on the systematic offering to the client under tourism standards; therefore, it has had little impact on the development of the region. The value chain of Wayúu gastronomy begins with the production of local products and their processing using ancestral techniques, culminating in an informal offer to the client. In conclusion, it is necessary to implement support and public policies for access to financing for formal enterprises, with their respective training, in order to satisfy the current growing demand in an efficient manner.